Response of acetyl-CoA carboxylase-resistant rice cultivars and advanced lines to florpyrauxifen-benzyl. (16th December 2020) - Sanders, Tameka L.; Bond, Jason A.; Lawrence, Benjamin H.; Golden, Bobby R.; Allen, Thomas W.; Famoso, Adam; Bararpour, Taghi
Abstract: Florpyrauxifen-benzyl and quizalofop were available for POST applications in 2018; however, little is known about the response of acetyl-CoA carboxylase (ACCase)–resistant rice cultivars and advanced lines to POST herbicides. A field study was conducted in 2017 and 2018 at Stoneville, MS, to characterize the response of ACCase-resistant rice cultivars and advanced lines to POST applications of florpyrauxifen-benzyl. The imidazolinone-resistant (IR) rice cultivars 'CL163' and 'CLXL 745', and ACCase-resistant rice cultivars 'PVL01', 'PVL013', 'PVL024-B', 'PVL038', 'PVL080', and 'PVL081'were treated with florpyrauxifen-benzyl at 0 (nontreated control for each cultivar) and 58 g ai ha –1 at the four-leaf to one-tiller (LPOST) growth stage. At 14 d after treatment (DAT), PVL01 was injured 5% to 6% greater than CLXL 745, PVL013, and PVL081; however, injury was ≤10% at that evaluation for all cultivars. Similarly, injury was ≤13% for all cultivars 28 DAT. Mature heights were reduced for all cultivars except PVL013 and PVL081. Rough rice yield was ≥100% of the control for all cultivars except PVL081, PVL013, and CL163. Results suggest that florpyrauxifen-benzyl can safely be applied POST to rice cultivars grown in Mississippi as well as ACCase-resistant cultivars that are currently under development.